(untitled) (Fiep Bulletin - online, 2024)
Introduction: This article describes the experience of a supervised internship at a Municipal School in the Municipality of Iranduba, where a Center at the State University of Amazonas (UEA) is located. Objective: To experience the didactic-pedagogical daily life of a Physical Education professional. Methods: It was a theoretical-practical research, with a qualitative study of a descriptive nature. The activities took place at the Creuza Abess Farah Municipal School, in Elementary School II, 6th A, B and C classes; 7° A and B; 8th A and B and 9th A and B, in the morning shift totaling 286 students. The thematic axes covered were; games and games, sports and fights. The sports practices developed were: futsal and volleyball. Games and games; adapted dodgeball, pass the ball and chain play. Fights: Taekwondo techniques. Results: The images show that the experiences during the internship were positive. Conclusion: We concluded that the experiences experienced in the supervised internship contributed to our academic training and professional practice.